2006
DOI: 10.1001/archinte.166.14.1512
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy for Somatization Disorder

Abstract: For patients diagnosed as having SD, CBT may produce clinical benefits beyond those that result from the current state-of-the-art treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
127
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(135 citation statements)
references
References 20 publications
4
127
0
4
Order By: Relevance
“…tients with functional symptoms who seek it, 24,25 we have found that CBT based on a functional explanation can be acceptable to relatively unselected neurology patients. Second, where should treatment be delivered?…”
Section: Data Collectionmentioning
confidence: 97%
“…tients with functional symptoms who seek it, 24,25 we have found that CBT based on a functional explanation can be acceptable to relatively unselected neurology patients. Second, where should treatment be delivered?…”
Section: Data Collectionmentioning
confidence: 97%
“…14, 15 Smith et al 14 reported on an intervention that led to more effective recognition and treatment of these patients in primary care. Allen et al 15 performed a controlled study of a time-limited cognitive behavior therapy (CBT)-type intervention on somatization disorder as defi ned by the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) in a mental health clinic.…”
Section: In T Erv En T Ion F or Une X Pl A Ined Sy Mp To Msmentioning
confidence: 99%
“…Allen et al 15 performed a controlled study of a time-limited cognitive behavior therapy (CBT)-type intervention on somatization disorder as defi ned by the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) in a mental health clinic. This intervention yielded signifi cant effects beyond those associated with a traditional consultation letter, ameliorating medically unexplained physical symptoms, improving functional status, and decreasing health care costs in a chronically ill population.…”
Section: In T Erv En T Ion F or Une X Pl A Ined Sy Mp To Msmentioning
confidence: 99%
“…3,4 The evidence base for CBT, in particular, includes effective support for patients with medically unexplained symptoms. 5 Due to clinical need and the presence of sound treatment options, this review is a welcome and timely exploration of non-invasive psychosocial treatments for patients suffering from orofacial pain.The authors start the presentation of their findings by stating that with respect to short-term outcomes, usual care performed better than psychosocial interventions in reducing pain intensity. However, in the long-term and after follow up, Dworkin selfcare interventions, habit reversal, and particularly CBT approaches (either with or without biofeedback) are significantly more effective in reducing pain intensity than usual care (or no care in the case of habit reversal).…”
mentioning
confidence: 99%
“…3,4 The evidence base for CBT, in particular, includes effective support for patients with medically unexplained symptoms. 5 Due to clinical need and the presence of sound treatment options, this review is a welcome and timely exploration of non-invasive psychosocial treatments for patients suffering from orofacial pain.…”
mentioning
confidence: 99%